JOANA D’ARC FÉLIX DE SOUSA - ENGLISH VERSION - Pinheiro, Bárbara Carine Soares (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Born in the interior of São Paulo and of poor social background, Joana D’arc graduated in Chemistry from the Campinas State University (UNICAMP) in 1986. She became a Master of Chemistry in 1990 and a Doctor of Science in 1994, also from UNICAMP. Currently, Dr. Joana works with tannery residues from the leather-footwear sector, interest that arised from a problem she had in her hometown where her father worked in a tannery and had difficulties in treating such residues. From this residues, the Brazilian scientist developed several technologies that are being transferred to the industry. Her researches, of great scientific and social relevance, earned several awards and consecrated her in one of the biggest names in Chemistry in Brazil.